MODERN METHODS OF TEACHING RUSSIAN LANGUAGE TO STUDENTS - Muqumova Gulnora (American Journals, 2022)
This article describes modern methods and methods of teaching Russian language to students based on interactive educational technologies. Effectiveness of education organized on the basis of interactive educational technologies, student activity is observed to increase.
Keywords: technology, education, method, traditional, non-traditional, interactive, mental